Semantic faceted search with aggregation and recursion - Sherkhonov, E; Cuenca Grau, B; Kharlamov, E; Kostylev, E (Springer, Cham, 2017)
Faceted search is the de facto approach for exploration of data in e-commerce: it allows users to construct queries in an intuitive way without a prior knowledge of formal query languages. This approach has been recently adapted to the context of RDF. Existing faceted search systems however do not allow users to construct queries with aggregation and recursion which poses limitations in practice. In this work we extend faceted search over RDF with these functionalities and study the corresponding query language. In particular, we investigate complexity of the query answering and query containment problems.